MODERN STRATEGY IN TREATMENT OF PERITONEAL CARCINOMATOSIS - A. A. Zakharenko; D. A. Zaitcev; M. A. Belyaev; A. A. Trushin; O. A. Ten; A. S. Natkha; K. N. Vovin; V. A. Rybalchenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2017)
Peritoneal carcinomatosis (PC) is a common manifestation of progression in peritoneal and gynecologic malignancies. Current primary strategy in treatment of PC is the concept of regional influence by the way of cytoreductive surgery and intraperitoneal chemotherapy, which has proven the efficiency in treatment of common appendicitis tumors, peritoneum mesothelioma, advanced colorectal cancer, ovarian and gastric cancers. However, in spite of the existing unified criteria for performing cytoreductive surgeries, we observe a lack of a standardized approach for intra-peritoneal chemotherapy, which is used in various variants and regimens in modern clinical practice. Further studies of effectiveness of various intra-peritoneal chemotherapy methods and their combinations are necessary for the development of modern algorithms in treatment of PC.